“What a Soul in Those Soaring Shapes”: Transcaucasia in XIX century British Writing - Nuralova, Stella (Armenian Folia Anglistika, 2005)
In his work “Transcaucasia and Ararat”, J. Bryce, the founder of the Anglo-American company, refutes the stereotypes about the Transcaucasia, reveals the true picture of ethnic cooperation in the region and presents the interest of the English toward Mount Ararat. The book by yet another author – H.F. B, “Armenia: Journey and Investigation” is a combination of two separate journeys from 1893 to 1898. Lynch is quite enthusiastic about the “mountain of the Ark, the mythical paradise”. Finally, in his collection of sonnets titled “The Purple East” W. Watson defends the dying nation, “a homeless nation” which “is stretching its arms in a prayer”. The works of the authors mentioned need further and detailed research especially in our days, when the new world order is underway.